IgG4-Related Disease Causing Facial and Recurrent Laryngeal Nerve Palsies: A Case Report - Farahani, Marjan Rahimi; Alesaeidi, Samira; Hosseini, Mohammad Mehdi Eshagh; Nozarian, Zohreh; Yazdani, Nasrin (Journal of clinical and diagnostic research, 2019)
Immunoglobulin G4-Related Disease (IgG4-RD) is a systemic fibro-inflammatory disorder. It can affect many different organs and tissues including salivary glands, orbits, retroperitoneum and many others. Neurological involvement by IgG4-RD is rare and its early diagnosis is important to avoid permanent organ dysfunction and disability. The effects of medications have not been evaluated adequately and need to focus on. So, in this article we present a rare case of IgG4-RD with parotid mass and facial and recurrent laryngeal nerve palsies which was successfully treated with rituximab and oral prednisolone.